IMPLEMENTATION OF SYSTEM THEORY IN EDUCATIONAL MEDIA FOR EARLY MARRIAGE CASES IN YOGYAKARTA - Al Firda, Ainul Luthfia (QAULAN: Journal of Islamic Communication, 2021)
Early marriage is an issue that is widely discussed around the world. Because the discourse of early marriage is often motivated by several factors that deviate from a child's justice rights. Even the issue of early marriage is also referred to as part of child abuse. The factors that cause early marriage are parents, economy, social and customary pressures, perpetuating relationships, social media and influencers, unwanted pregnancy, lack of reproductive health education for children and parents. PKBI is one of the institutions whose concentration focuses on the study of sexual and reproductive health for all parties providing several means to voice the importance of suppressing the increase in the rate of early marriage, especially in Yogyakarta. One of the efforts made by PKBI is to hold several discussion forums. The holding of discussions is one of the comprehensive efforts to educate adolescents and parents about the importance of sexual and reproductive health, which in turn can hamper the process of early marriage. Keywords: Early Marriage, Reproductive Health Education, Early Marriage Factors, Communication